The Evaluation Process of Using a Pedestal Tray, Four Pairs of Joss-Sticks, and Candles in the Homage Competition at the 70th National Student Arts and Crafts Competition - Waichiangkha, Akkarapol; Fuangsri, Kanchana; Anekthanasup, Ittipon (Journal of Cultural Approach, 2023)
The Office of the Basic Education Commission set a student art and crafts competition for students to express their knowledge and abilities. The 70th National Student Arts and Crafts Competition offered a pedestal tray with four pairs of joss-sticks and candles for paying homage in the competition, which are important and popular when praying and in various auspicious ceremonies. In terms of the competition criteria, qualifications and types of competitors, the application and details of the competition, and criteria for scoring needed to be agreed upon considering the process, criteria consideration, and evaluations of the pedestal tray, joss-sticks, and candles the pre-competition process, competition process, and post competition process which were important evaluation process.